The evolution of bargaining under austerity. Political change in contemporary French and German labor-market reform - Vail, Mark I. (Köln, 2007)
"This paper examines the relationship among economic context, political institutions, and the political dynamics of adjustment within national models of capitalism through an analysis of recent labor-market reform in France and Germany. It argues that a climate of economic austerity since the 1970s, combined with the political legacies of earlier policy-making models and their failure to confront the challenges of slow economic growth and high rates of unemployment, have led to qualitative shifts in the incentives facing government officials and key interest groups. These shifts have produced new patterns of politics - "competitive interventionism" in France and "conflictual corporatism" in Germany - within generally stable formal institutional configurations. The paper explores the implications of the French and German experience for scholarly understandings of policy making in advanced industrial societies in a climate of economic austerity and how it differs from policy making under conditions of prosperity. In light of this analysis, it calls for a rethinking of prevailing conceptions of the relationship between formal institutional structures and the dynamics of bargaining and state-society relations across varying economic and historical contexts."